Phenotypic characterization of the creole goat in the southern highlands of Peru: A first step toward the sustainable use of a forgotten zoogenetic resource - Sessarego Davila, Emmanuel Alexander (2025)
Background: Five hundred years ago, goats were introduced to Peru, and since then, they have adapted to different climatic conditions, giving rise to the Creole goat, characterized by showing greater rusticity and better quality in both milk and meat than specialized breeds. Aim: This study aimed to describe the phenotype of the Creole goat in the Highlands of Chincha province, Ica. Methods: A total of 146 females aged >2 years without signs of crossbreeding with specialized breeds from the districts of San Juan de Yanac, San Pedro de Huacarpana, and Chavin were evaluated. Six phaneroptic characteristics, nine morphometric characteristics, and nine zoometric indices were registered. Tables and bar graphs were prepared. The chi-square test was performed to determine the association between districts and phaneroptic variables, ANOVA to identify differences between districts, correlation coefficients to evaluate morphostructural harmonicity, and multiple regression analysis to predict the live weight of animals. Results: Of the goats, 61.6% had a spotted coat, 59.6% had no beard, 75.3% had horns, 57.5% had parallel teats, 90.4% had no wattles, and 80.8% had the correct number of teats, showing an association between district and absence/ presence of beard (p = 0.001). All morphometric parameters and zoometric indices were homogeneous within each district, with differences between districts (p < 0.05). Conclusion: The Creole goat of the high Andean area of Chincha is characterized by presenting a high morphostructural harmony, being medium to large in size, brevilineal, convexilinear and having a productive aptitude with a tendency to double purpose.